Faster than history = Historiaa nopeammin : contemporary perspectives on the future of art in the Baltic countries, Finland and Russia = näkökulmia nykytaiteen tulevaisuuteen Baltian maissa, Suomessa ja Venäjällä - KIASMA (Museum of Contemporary Art), Helsinki (Helsinki : KIASMA (Museum of Contemporary Art) Helsinki, 2004)
The Blue Noses Group ; Chernyshev, Aristarkh ; Efimov, Vladislav ; Famous Five ; Gabrans, Gints ; Gelzis, Kristaps ; Gudaitis, Arünas ; Jeleznikov, Mikhail ; Kaila, Tuukka ; Laanemets, Mari ; Sukmit, Killu ; Merila, Herkki-Erich ; Tammiksaar, Arbo ; Petljura, Alexander ; Ragimov, Kerim ; Rainio, Minna ; Roberts, Mark ; Rakauskaité, Giedré LilienéEglé ; Semper, Ene-Liis ; Stasiulytè, Laura ; Sydorenko, Viktor ; Vilensky, Dmitry ; Viljus, Mart
Engels, Fins
Exhibition. Faster than history. KIASMA (Museum of Contemporary Art) Helsinki. 2004-01-31. 2004-05-02. Contemporary perspectives on the future of art in the Baltic countries, Finland and Russia
boek